Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3847/1538-4357/ac32bd
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Spectral Characteristics of Three Flaring Gamma-Ray Quasars Observed by VERITAS and Fermi-LAT

Abstract: Flat-spectrum radio quasars (FSRQs) are the most luminous blazars at GeV energies but only rarely emit detectable fluxes of TeV gamma rays, typically during bright GeV flares. We explore the gamma-ray variability and spectral characteristics of three FSRQs that have been observed at GeV and TeV energies by Fermi-LAT and VERITAS, making use of almost 100 hr of VERITAS observations spread over 10 yr: 3C 279, PKS 1222+216, and Ton 599. We explain the GeV flux distributions of the sources in terms of a model deriv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 87 publications
1
30
0
Order By: Relevance
“…We set a fairly high autocorrelation parameter of f = 0.95, consistent with the absence of a resolvable spectral break in the gamma-ray PSD of 3C 279 as determined both by CARMA modeling (Ryan et al 2019) and by the power spectral response method (Goyal et al 2021). With these parameters, α obs ≈ 2.3, similar to the best-fit values of λ + 1 = 1.7 and 2.0 reported, respectively, by Tavecchio et al (2020) and Adams et al (2022).…”
supporting
confidence: 83%
See 4 more Smart Citations
“…We set a fairly high autocorrelation parameter of f = 0.95, consistent with the absence of a resolvable spectral break in the gamma-ray PSD of 3C 279 as determined both by CARMA modeling (Ryan et al 2019) and by the power spectral response method (Goyal et al 2021). With these parameters, α obs ≈ 2.3, similar to the best-fit values of λ + 1 = 1.7 and 2.0 reported, respectively, by Tavecchio et al (2020) and Adams et al (2022).…”
supporting
confidence: 83%
“…2 Tavecchio et al (2020) showed that this PDF provides a satisfactory representation of the gamma-ray flux distributions of six bright FSRQs observed by Fermi-LAT using the light curves analyzed by Meyer et al (2019). Subsequently, Adams et al (2022) demonstrated that this model provides a better fit than a lognormal PDF to the Fermi-LAT flux distributions of three bright FSRQs, 3C 279, PKS 1222+216, and Ton 599.…”
Section: Background and Related Workmentioning
confidence: 99%
See 3 more Smart Citations